Enzymes and/or combination of organic acid and essential oils supplementation in pasture-fed free-range laying hens increased the digestibility of nutrients and non-starch polysaccharides. (10th October 2018) - Iqbal, Zafar; Metzger, Florian; Singh, Mini; Morgan, Natalie; Swick, Robert A; Perez-Maldonado, Rider A; M'Sadeq, Shawkat A; Zentek, Jürgen; Ruhnke, Isabelle
ABSTRACT: Pasture intake can be a major challenge for free-ranging hens. This study was conducted to examine pasture digestion and to manage its negative effects. A total of 300 ISA Brown laying hens were used to investigate the effect of time on range (T) in short-term (6 wk) and long-term (12 wk) of 2 range types (R) (gravel vs. pasture) and dietary supplements (F) (T1 = xylanase; T2 = xylanase/beta-glucanase/pectinase/protease; T3 = xylanase/benzoic acid/essential oils) on crude protein, crude fiber, acid detergent fiber, neutral detergent fiber, non-starch polysaccharides (NSP), calcium and phosphorus digestibility, pH of the crop, and ileum digesta viscosity and morphology. Hens exposed to the range for 12 wk had lower ( P < 0.05) digestibility of crude protein, insoluble rhamnose, ribose, and lower ileal pH compared to hens that ranged for 6 wk. Hens ranging on pasture had lower digestibility ( P < 0.05) of crude protein, acid detergent fiber, neutral detergent fiber, insoluble arabinose, and insoluble xylose, but higher digestibility ( P < 0.05) of insoluble mannose and glucose compared to hens that ranged on gravel. Hens fed T2 and T3 had higher digestibility ( P < 0.05) of CP, acid detergent fiber, and neutral detergent fiber compared to hens fed T1. Hens fed T2 had higher digestibility ( P < 0.05) of free oligosaccharide arabinose and xylose than those fed T1 or T3 diets. A significant interaction between T × R was detected for crude fiber digestibility and villus height. Digestibility of crude fiber was reduced and villus height was increased in hens ranged on pasture for 12 wk compared to 6 wk. An interaction between R × F was observed on phosphorus and soluble NSP digestibility ( P < 0.05). Hens fed T2 and T3 diets had lower digestibility of phosphorus and NSP on gravel than on pasture. In conclusion, pasture consumption impaired the digestibility of nutrients. Supplementing free-range diets with a multi-enzyme or xylanase/benzoic acid/essential oil product reduced these negative effects and increased the ileal nutrient digestibility.